The awareness of water intake and its correlation with BMI among students attending national and international secondary schools in Riyadh, Saudi Arabia. Issue 1 (1st January 2021) - Ahmeda, Ahmad F.; Al-Ahmadi, Thamer F.; Alotaibi, Abdullah F.; Alshehri, Mohammed A.; Almousa, Abdulelah M.; Alshehri, Omar M.; Alanazi, Abdulrahman Z.; Anweigi, Lamyia M.
ABSTRACT: Dehydration is linked to worse cognitive functions and preference for beverages that are linked to obesity and other health conditions. Saudi Arabia's hot climate can exacerbate these effects and it is important to ensure that children in the region understand the benefits of adequate water intake. To evaluate secondary school student perceptions and practices regarding water intake, investigate how water intake is related to BMI and school performance, and compare international schools to national schools. This cross-sectional study surveyed understanding and practices relating to water intake of national and international secondary school students using a questionnaire based on a random selection of schools and students. One-hundred and sixty-two students from international schools (I) and 157 from national schools (N) responded. Most were aged 16 and 17 years old (I:61.1%, N:76.5%, p = .005). The average BMI of all students was 24.9 ± 6.013 (I:23.6 ± 4.658, N:26.1 ± 6.931, p < 0.001). Students understood beverages do not replace water intake (I:80.2%, N:75.8%, p = .337) and preferred water when thirsty (I:77.8%, N:75.2%, p = .549). However, water consumption was low with more than 50% of students drinking less than 1500 ml a day (I:54.3%, N:70.7%, p = .002). A positive correlation between BMI and water intake was observed only among international school students. Students have inadequate water intake despite understanding the importance of hydration. There are some differences between international school students and national school students that can be attributed to the availability and sources of water, though other factors cannot be excluded.